Membina Aktivitas Belajar Mahasiswa di Perguruan Tinggi Melalui Metode TIE (Translation, Interpretation, Extrapolation) pada Masa Pandemi Covid-19 - Zulhafizh, Zulhafizh (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
The research objective is to foster student learning activities through the TIE (Translation, Interpretation, Extrapolation) method. The research method used was descriptive correlational method. The research sample consisted of 75 people. The data instrument was in the form of a Likert scale questionnaire which consisted of the aspects of translation, interpretation, and extrapolation. Data analysis technique used descriptive statistics, Product Moment correlation, chi square normality, and Anova. The result of the study showed that the average score for translation was 3,767 which was in the high category; the average score for interpretation was 4,075 categorized as very high; and the exploration average score was 4,065 categorized as very high. Overall, it was at an average of 3,969 which was in the high category. If the translation, interpretation, and extrapolation activities were carried out properly, it could build up to 99,3% of learning activities. In conlcusion, the TIE method is important to apply in independent learning activities because it can stimulate students' cognition and psychomotor to achieve better learning quality. In addition, it can present insightful and experienced students.